2017
DOI: 10.1016/j.jhin.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Screening for sepsis in general hospitalized patients: a systematic review

Abstract: Clinicians, researchers and health decision-makers should consider these findings and limitations when implementing screening tools, research or policy on sepsis recognition in general hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 39 publications
0
28
0
4
Order By: Relevance
“… 13 The studies that found no effect on ICU LOS varied in setting, with 1 implemented in the ED, 1 in a medical ICU, and 1 in all noncritical care units. 21 One study attributed lack of impact on ICU LOS to a PMS with poor predictive value, 9 and one credited the already vigilant ICU staff 12 ; the third was underpowered to detect modest changes in ICU LOS. Two studies reported on ICU transfer rate, and neither found a significant effect on this or any other outcome measure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 The studies that found no effect on ICU LOS varied in setting, with 1 implemented in the ED, 1 in a medical ICU, and 1 in all noncritical care units. 21 One study attributed lack of impact on ICU LOS to a PMS with poor predictive value, 9 and one credited the already vigilant ICU staff 12 ; the third was underpowered to detect modest changes in ICU LOS. Two studies reported on ICU transfer rate, and neither found a significant effect on this or any other outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 11 , 13 , 17 , 22 , 23 In addition, 4 systematic reviews covered this topic to some degree. 21 , 24 26 The most commonly reported process measure was time to antibiotic administration (n = 8), followed by time to lactate measurement and blood culture draw (n = 5 each), and time to fluid administration (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(45) Other studies have demonstrated high sensitivity and specificity in the detection of sepsis with the use of screening tools, both electronic and manual, but more studies are needed to determine the effectiveness of each type of alert. (46-50) Despite this, there were no difficulties in the implementation or overload of the work of the medical or nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…(144) Negli ultimi anni si è notato un aumento della presa in carico dei pazienti con sepsi all'interno dei reparti medici e chirurgici e, in diversi paesi del Nord America e dell'Europa, è segnalato che il 14-80% dei pazienti ricoverati in tali reparti sviluppa sepsi. (148) Come per l'infarto miocardico acuto, lo stroke e il politrauma, anche per la sepsi sono stati riscontrati outcomes migliori quando è presente l'identificazione precoce e una gestione appropriata del quadro settico nelle ore iniziali,(145) e l'infermiere svolge un ruolo centrale ed attivo durante tutto il percorso di cura. Trattandosi di una sindrome difficile da diagnosticare l'identificazione precoce è fondamentale per la corretta gestione del quadro settico; affinché ciò avvenga è necessario che l'infermiere abbia competenze avanzate non solo per la valutazione delle condizioni cliniche, che può avvenire anche attraverso l'uso discale di valutazione, ma soprattutto per la valutazione del rischio di sviluppare la sepsi.…”
Section: La Sepsiunclassified